Accessing the role of Joule heating on densification during flash sintering of YSZ. (1st April 2022) - Bhandari, Subhadip; Mishra, Tarini Prasad; Guillon, Olivier; Yadav, Devinder; Bram, Martin
Abstract: Flash sintering is a novel electric field and current assisted sintering technique which densify ceramics at moderate furnace temperature and in short time (few seconds) as compared to the conventional sintering techniques. The onset of flash encompasses three unique characteristics, (i) non-linear rise in conductivity, (ii) luminescence and (iii) rapid densification. the mechanism behind the flash phenomena is not fully understood yet. The present work experimentally demonstrated that the densification in flash sintering is primarily dominated by Joule heating. Herein, we distinguished the onset of flash and the degree of densification of cubic zirconia in sintering atmospheres with different oxygen partial pressures. In this study, we demonstrate that the flash onset temperature and densification are independently influenced by the sintering atmosphere during flash sintering. Furthermore, the extent of densification is not directly influenced by the current density rather, by the power dissipated in the sample. Graphical abstract: Image, graphical abstract